Formação inicial de professores de ciências e inclusão escolar: um olhar para as experiências de estágio - Silva, Elisa Ramos da (2019)
This study focused on the initial training of science teachers in the perspective of Inclusive Edu-cation (IE), with emphasis on the experiences during the internship. In Brazil, in most cases, students with Special Educational Needs (SEN) are still marginally inserted into regular class-rooms. One of the reasons refers to the deficits in initial and continuing teacher training, which discourages the inclusion of these students. Therefore, the teacher's preparation for attending students with disabilities and/or SEN is indispensable for the teaching-learning process to be consolidated. The objective of this research was to analyze if the experiences proposed by the science teaching training promote discussions, reflections and practices orientated towards the IE. For the data collection, the reports of the supervised internship were analyzed in: Sciences I and II; Biology I. Subsequently, self-filling instruments (SFIs) were applied to all the students from those disciplines and the teachers who was responsible for the internships. The research was based on Historical-Cultural Theory (HCT) and the Critical Historical Pedagogy (CHP). The analysis of the data was made from the historical-dialectical materialism, which investigates the phenomenon from a perspective of totality, considering the complexity of social realities and their historical significance. Consequently, it seeks to identify the connections between the dif-ferent aspects that characterize a certain reality. The results showed that there are reports about the subject in the internship final project and discussions about IE in the internship classes and other classes. However, these discussions can be low priority and with little theoretical and methodological discussion, since there is no compulsory subject in the area. Which we consider fundamental for training the future teachers of this undergraduation to the inclusion of students with disabilities and/or SEN in the regular classrooms.